IDENTIFICATION OF ENDOPYTIC FUNGI COMPOUND ON WHITE WEED LEAVES (Ageratum Conyzoides L.) CONTAINING THE POTENTIAL TO PRODUCE ANTIBIOTICS BY TLC-BIOAUTOGRAPHY. - Rofika, Evi; Fitriana, Fitriana; Herwin, Herwin (Journal Microbiology Science, 2023)
White weed (Ageratum conyzoides L.) is known to have antibacterial elements containing chemical compound such as saponin and flavonoids. This study aimed to examine the antibiotic activity of endophytic fungi isolates of white weed leaves by the TLC-Bioautography method. The results of endophytic fungi isolation of white weed leaves obtained 10 isolates consisting of IFDP 1, IFDP 2, IFDP 3, IFDP 4, IFDP 5, IFDP 6, IFDP 7, IFDP 8, IFDP 9, and IFDP 10. The results of the macroscopic examination of the ten isolates of endophytic fungi found different characteristics. The results of the screening using 9 samples obtained isolates that found activity showing high inhibitory power, such as IFDP 1, IFDP 2, and IFDP 4 isolates. Isolates of IFDP 1, IFDP 2 and IFDP 4 were fermented on MYB medium for 14 days. Then filtering and evaporation were carried out to produce an extract. Isolate fermentate extracts were identified using Thin Layer Chromatography with chloroform eluent: methanol (4:2). The antibiotic activity test was done using TLC-Bioautography method, and obtained an Rf value in isolate 1, at Rf 0.74 on Vibrio cholerae. Isolate 2 resulted rf value of 0.67 on Salmonella thypi, Vibrio cholerae, Eschericia coli, disentriae, Staphylococcus epidermis. Isolate 4 generated an Rf value of 0.74 on Pseudomonas aeruginosa and Vibrio cholerae. While the group of active chemical components contained in the endophytic fungi isolates of white weed leaves was lavonoids by using AlCl3 reagents, AICI3 reagent alkaloids, and Sulfuric acid for saponin identification